Digitalisation of Pesantren through Pegon Keyboard Virtual and Rumah Kitab in Preserving the Archipelago's Khazanah and Islamic Studies - Mamlu’ah, Aya; Rohmawati , Ulva Badi'; Nahdlatul , Ririn Fauziyah; Mahfudoh, Sitti Atiyatul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
Integrating digital technology into Islamic boarding schools (pesantren) is increasingly essential to preserve and revitalise traditional Islamic education in response to modern pedagogical demands. This study employed a Research and Development (R&D) approach utilising the ADDIE model—analysis, Design, Development, Implementation, and Evaluation—focusing on the initial development phase. The primary objective was to design a digital learning tool that supports using the Pegon script and the broader Islamic intellectual heritage of the archipelago. Data were collected through in-depth interviews with pesantren stakeholders, including ustadz/ustadzah, students (santri), and religious institutional representatives. Feasibility assessments were conducted through expert and practitioner validation using content, language, and visual presentation questionnaires. Qualitative data were analysed through reduction, presentation, and conclusion drawing, while quantitative data were processed using eligibility percentage calculations. The results indicated that the developed virtual Pegon keyboard and rumah kitab (digital book repository) prototypes were categorised as